Measuring catatonia motor behavior with objective instrumentation - von Känel, Sofie; Nadesalingam, Niluja; Alexaki, Danai; Baumann Gama, Daniel; Kyrou, Alexandra; Lefebvre, Stéphanie; Walther, Sebastian (Frontiers in Psychiatry, 2022)
Objective: Catatonia is a neuropsychiatric syndrome, with important psychomotor features, associated with schizophrenia and other psychiatric disorders. The syndrome comprises multiple symptoms including abnormal motor control, behaviors, volition, and autonomic regulation. Catatonia assessment relies on clinical rating scales and clinicians familiar with the catatonia exam. However, objective instrumentation may aid the detection of catatonia. We aimed to investigate the relationship between movement parameters derived from actigraphy and expert ratings of catatonia symptoms measured by the Bush Francis Catatonia Rating Scale (BFCRS) and the Northoff Catatonia scale (NCS). Methods: Eighty-six acutely ill inpatients with schizophrenia spectrum disorders were assessed with the BFCRS, the NCS, and 24 hour continuous actigraphy. Non-wear and sleep periods were removed from the actigraphy data prior to analysis. Associations between total catatonia scores, derived from both BFCRS and NCS, and actigraphy parameters as well as between single BFCRS items and actigraphy parameters were calculated using Spearman’s rank correlation and non-parametric ANCOVAs (Quade’s ANCOVAs), respectively. Results: Both higher BFCRS total scores (r = 0.369, p = 0.006) and NCS total scores (r = 0.384, p = 0.004) were associated with lower activity levels (AL). Higher scores on single BFCRS items such as immobility/stupor or staring were linked to lower AL (immobility/stupor: F = 17.388, p <0.001, η² = 0.175; staring: F = 7.849, p = 0.001, η² = 0.162) and lower metabolic equivalents of task (MET). Conclusion: Specific catatonia symptoms such as immobility/stupor and staring can be measured with actigraphy. This may aid the detection, staging, and monitoring of catatonia in clinical settings.